Organotypic Culture of Neonatal Murine Inner Ear Explants - Ogier, Jacqueline M.; Burt, Rachel A.; Drury, Hannah R.; Lim, Rebecca; Nayagam, Bryony A. (Frontiers in Cellular Neuroscience, 2019)
The inner ear is a complex organ containing highly specialised cell types and structures that are critical for sensing sound and movement. In vivo, the inner ear is difficult to study due to the osseous nature of the otic capsule and its encapsulation within an intricate bony labyrinth. As such, mammalian inner ear explants are an invaluable tool for the study and manipulation of the complex intercellular connections, structures, and cell types within this specialised organ. The greatest strength of this technique is that the complete organ of Corti, or peripheral vestibular organs including hair cells, supporting cells and accompanying neurons, is maintained in its in situ form. The greatest weakness of in vitro hair cell preparations is the short time frame in which the explanted tissue remains viable. Yet, cochlear explants have proven to be an excellent experimental model for understanding the fundamental aspects of auditory biology, substantiated by their use for over 40 years. In this protocol, we present a modernised inner ear explant technique that employs organotypic cell culture inserts and serum free media. This approach decreases the likelihood of explant damage by eliminating the need for adhesive substances. Serum free media also restricts excessive cellular outgrowth and inter-experimental variability, both of which are side effects of exogenous serum addition to cell cultures. The protocol described can be applied to culture both cochlear and vestibular explants from various mammals. Example outcomes are demonstrated by immunohistochemistry, hair cell quantification, and electrophysiological recordings to validate the versatility and viability of the protocol.